Clinical characteristics, management, and outcomes of acute heart failure patients in Central Asia. (25th January 2023) - Abdurashidova, T; Muller, M; Dzhorupbekova, K; Kaliev, K; Chazymova, Z; Toktosunova, A; Beishenkulov, M; Kirsch, M; Hullin, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiovascular disease (CVD) is the leading cause of death in Central Asia. In 2019, crude mortality rate in the region was 348.13 per 100, 000 population. Heart failure (HF) is important CVD subtype owing to even worse outcome. There has been a dearth of information on the epidemiology of HF in Central Asia. Purpose: we aimed to describe aetiology, comorbidities, adherence to guideline-directed medical therapy (GDMT), and outcomes in patients hospitalised for heart failure in Central Asian population. Methods: the retrospective analysis included 538 patients hospitalised for decompensated heart failure in a tertiary hospital from December 2011 to December 2019. Inclusion criteria were (i) age ≥18 years; (ii) hospitalisation for HF treatment. Exclusion criteria were (i) pregnancy; (ii) comorbidity with survival time considered to be <1 year on the basis of patients` medical history; (iii) acute HF caused by acute myocardial infarction, metabolic, toxic or infectious disorders. Primary outcome was one-year all-cause mortality, secondary outcome - readmission for HF at one year. Given that the data had been collected retrospectively, informed consent was not obtained, nevertheless, local ethics committee approved the study. Results: Central Asian patients were relatively young (mean age 64.0 years), 61.2% of them were male, 77.7% had ischemic heart disease, 8.7% rheumatic heart disease, 32.2% obstructive pulmonary disease, 47.7% atrial fibrillation/flutter, 45.7% hyperlipidemia, 72.1% hypertension, and 31.6% diabetes mellitus. Use of GDMT at discharge was 76.0% for beta-blockers, 29.7% for angiotensin-converting enzyme inhibitors, 21.2% for angiotensin II receptor blockers, 71.9% for mineralocorticoid receptor antagonists. Only 3.9% of patients were implanted with a pacemaker and 0.9% with an implantable cardioverter defibrillator. All-cause mortality at one year was 19.0%, with no difference between patients with preserved and reduced ejection fraction (14.9 vs. 19.9%, p=0.243). However, patients with preserved ejection fraction were less likely to experience a readmission for heart failure at one year (13.9 vs. 29.3%, p=0.002). Conclusions: results of the analysis showed that Central Asian patients are relatively young, mostly male, with high prevalence of ischemic heart disease, and reduced ejection fraction, and lower rate of GDMT use and device therapy.